Cryptography Based Secure Image Transfer To Mobiles - SHIVAKUMAR M (2005)
INTERNAL GUIDE : Rao R Swarnalatha . EXTERNAL GUIDE : Mohideen USN No : 1MJ04SCS14 CARRIED OUT AT : Rec Accent Bangalore-560 018 ACC NO : PC32
Keywords: M.Tech Computer Science